2016
DOI: 10.11138/ccmbm/2016.13.1.038
|View full text |Cite
|
Sign up to set email alerts
|

Atraumatic intracapsular neck of femur fractures after prolonged bisphosphonate treatment: a new atypical variant?

Abstract: SummaryWe present 2 cases of elderly females presenting with atraumatic, near-vertical (Pauwells grade 3), intracapsular neck of femur fractures. Following diagnosis of osteoporosis on DEXA scans, they had received alendronic acid for 7 and 10 years respectively. Routine blood tests and serum estimations of calcium, vitamin-D and thyroidstimulating hormone, done at admission, were within the normal ranges. These patients were managed with a hemiarthroplasty and a dynamic hip screw (DHS) respectively, following… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 12 publications
1
11
0
Order By: Relevance
“…Several cases of such fractures were reported to date. Previous reports described patients treated with different BPs—alendronic acid (three patients), cyclical etidronate (one patient) and one with ibandronic acid similar to the patient in this study [ 11 14 ]. Although treatment with BPs is highly recommended and commonly prescribed for osteoporosis to reduce the risk of hip fracture, preceding case reports show that it may also provoke femoral neck fracture.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Several cases of such fractures were reported to date. Previous reports described patients treated with different BPs—alendronic acid (three patients), cyclical etidronate (one patient) and one with ibandronic acid similar to the patient in this study [ 11 14 ]. Although treatment with BPs is highly recommended and commonly prescribed for osteoporosis to reduce the risk of hip fracture, preceding case reports show that it may also provoke femoral neck fracture.…”
Section: Discussionsupporting
confidence: 61%
“…All of the non-traumatic femoral neck fractures associated with BPs treatment were only described in women aged over 77 [ 11 14 ]. This is because BPs are mostly prescribed in older patients (our patient was only 57).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 10 , 11 Furthermore, some authors have suggested that manifestation is also possible in the intracapsular part of the femur neck. 12 …”
Section: Evaluation and Diagnosismentioning
confidence: 99%
“…Elderly hip fractures until now have been considered as "typical" [5] of fragility arising from osteoporosis but the stress basicervical fractures of the femoral neck, secondary to the prolonged use of bisphosphonates, have been reported since 2002 [24][25][26][27][28] and today this "atypical" variant has been reported in four opportunities one of them bilateral [24] . The basicervical fracture of our case is like one presented by two of these authors [25,26] the others correspond to the classic description of fractures of the femoral neck due to stress [27,28] .…”
Section: Discussionmentioning
confidence: 99%